How do you solve x+y+3 and 2x+3y=9?
Answers
Answered by
0
there is one error that is x+y=3 not +3
x+y=3
y=3-x
2x+3(3-x)=9 [y=3-x]
2x+9-3x=9
2x-3x=0
-x=0
X=0
y=3-x
y=3-0=3
check
2*0+3*3=9
0+9=9
9=9
LHS=RHS
Answered by
5
To solve this equation we need to apply substitution method :
x + y + 3 => x + y = 3 -------- (1)
2x + 3y = 9 -------- (2)
From eq (1)
x = 3 - y
Now substituting value of x in eq (2)
2x + 3y = 9
2( 3 - y ) + 3y = 9
6 - 2y + 3y = 9
6 + 3y - 2y = 9
6 + y = 9
y = 9 - 6
y = 3
Now substituting the value of y in eq(1)
x + y = 3
x + 3 = 3
x = 3 - 3
x = 0
∴ Value of y is 3 and value of x is 0
Similar questions